Developed an Approach to Monitor the Technical Conditions of the Wheels by Measuring the Rolling Stock-track Forces - Waail Lafta; R.V. Rahimov; O.B. Nigmatov (International Journal of Machine Systems and Manufacturing Technology, 2023)
With the rapid development of railway transportation, there is a growing need to improve the method of measuring the impact force exerted by rolling stock on the rail track. Monitoring the technical conditions of the rail track and wheels is crucial. This research aimed to investigate the improvement of existing systems for wheel monitoring during operation and propose a method to develop rolling stock diagnostic systems while the train is in motion. The study focused on extending the track measuring zone to ensure the comprehensive detection of defects across the entire rail wheel, considering the speed and axle load of the rolling stock. By considering these factors, the researchers aimed to optimize the detection of defects in the rolling stock wheels. The parameters of the inter-sleeper gap on the railway track and the optimal length of the measuring track for defect detection were determined based on the research findings. Furthermore, the study also determined the permissible speeds for rolling stock on the rail-measuring track. This information is crucial for ensuring safe and efficient operations while conducting measurements and diagnostics on the rolling stock. This research contributes to advancing rolling stock monitoring and diagnostics by proposing improvements to existing systems and providing insights into optimizing the measurement process. By accurately detecting defects and determining permissible speeds, this research aids in enhancing the safety and reliability of railway transportation systems.
Keywords: Rolling stock; TGMV; railway track; stress; transportation